Clinical Leadership and Integration of Triple Bottom Line for Planetary Health - Wasim Alamgir; Hina Shan (Life and Science)
The accelerating global concern of climate change and its link with human health requires sustainability to be a crucial part of healthcare quality. The protection of planetary health in the context of ecological and social determinants of health require the integration of all aspects of health services including the professionals, management, and administration. Clinical health professionals particularly hold a critical position in this scenario, as they are mandated to protect individuals and communities from diseases caused or accelerated by environmental factors. Therefore, to combat the negative impacts of climate change on human health, the trusted voice of clinicians needs to be raised for communicating climate risks and solutions to patients, the public, and policymakers.